ВЛИЯНИЕ ДАВЛЕНИЯ НА СВОЙСТВА МДП СТРУКТУР - Исмайлов, Б.К.; Аметов, Р.А.; Нурниязов, П.К. (SCIENCE and SOCIETY, 2020)
The article investigated the effect of hydrostatic pressure on the relaxation characteristics of three-layer structures Al-n-Si -SiO2-Al. It was found that, for 15÷20 min, a pressure of 8 kbar leads to a decrease in the integral density of the state surface without affecting the generation centers in the volume.
Keywords: MDS construction; hydrostatic pressure; Schottky diode